High Diversity of Anaerobic Alkane-Degrading Microbial Communities in Marine Seep Sediments Based on (1-methylalkyl)succinate Synthase Genes - Stagars, Marion H.; Ruff, S. Emil; Amann, Rudolf; Knittel, Katrin (Frontiers in Microbiology, 2016)
Alkanes comprise a substantial fraction of crude oil and are prevalent at marine seeps. These environments are typically anoxic and host diverse microbial communities that grow on alkanes. The most widely distributed mechanism of anaerobic alkane activation is the addition of alkanes to fumarate by (1-methylalkyl)succinate synthase (Mas). Here we studied the diversity of MasD, the catalytic subunit of the enzyme, in 12 marine sediments sampled at seven seeps. We aimed to identify cosmopolitan species as well as to identify factors structuring the alkane-degrading community. Using next generation sequencing we obtained a total of 420 MasD species-level operational taxonomic units (OTU0.96) at 96% amino acid identity. Diversity analysis shows a high richness and evenness of alkane-degrading bacteria. MasD-based similarity of alkane-degrading communities was highest at sites with similar hydrocarbon composition; the MasD community structure is clearly driven by the hydrocarbon source available at the various seeps. Two of the detected OTU0.96 were cosmopolitan and abundant while 75% were locally restricted, suggesting the presence of few abundant and globally distributed alkane degraders as well as specialized variants that have developed under specific conditions at the diverse seep environments. Of the three MasD clades identified, the most diverse was affiliated with Deltaproteobacteria. A second clade was affiliated with both Deltaproteobacteria and Firmicutes likely indicating lateral gene transfer events. The third clade was only distantly related to known alkane-degrading organisms and comprises new divergent lineages of MasD homologues, which might be an overlooked phylum of alkane-degrading bacteria. In addition, masD geneFISH allowed for the in situ identification and quantification of the target guild in alkane-degrading enrichment cultures. Altogether, these findings suggest an unexpectedly high number of yet unknown groups of anaerobic alkane degraders and underline the need for comprehensive surveys of microbial diversity based on metabolic genes in addition to ribosomal genes.